Konsepsi Masyarakat Madani Dalam Menegakkan Hak Asasi Manusia - Muhammad Pengkuh Wedhono Jati (CV. Ulil Albab Corp, 2023)
The conception of civil society is a form of egalitarian nationalism, equality of human rights, pluralism, democracy and open participation from all elements of citizens. The conception of civil society as a form of good governance in which there is good management, which is based on transparency, open participation and accountability in all citizen activities, so that a clean government is formed. This study uses the library study method with data collection techniques through an analysis of books or literature as well as various reports on the topic to be raised. The data used in this research comes from books, textbooks, journals, scientific articles or other literature that contains the concepts to be studied. The Medina Charter says that the nation-state is established on the basis of the unification of all elements of society into one nation without discriminating between the groups within it. With the madinah charter, a harmonious relationship is established and fulfills the rights as human beings who believe in giving good advice to each other, freely without cheating, because this becomes a social contract on the basis of honesty and conscience. Civil society with the social culture of NU members, namely mutual cooperation, nurturing and all social activities based on a sense of religiosity towards transcendent things.